Re (Imagining) Water Pedagogies in Early Childhood Education and Care Programs - Mathurin, Georgiana (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
This paper discusses possibilities of relational world making with water. Many Canadian early childhood education and care programs continue to engage water through a developmentalist lens, such as through practices that focus on containing, extracting, and trapping water. Children’s explorations, such as with sensory water bottles and water tables, are predominantly viewed through narrow learning and developmental milestones. This deficit perspective maintains colonial and commodified relations with water. This paper presents some ways children and early childhood educators can create liveable worlds with water.